2004
DOI: 10.1002/bin.165
|View full text |Cite
|
Sign up to set email alerts
|

Using video modeling to teach a domestic skill with an embedded social skill to adults with severe mental retardation

Abstract: We assessed whether three adults with severe mental retardation would acquire a domestic skill (making coffee) with an embedded social skill (serving coffee to and sitting down beside a peer) via video modeling procedures. Training was conducted in a classroom in the participants' day treatment setting. The intervention consisted of (i) watching a video of an adult with a developmental disability making coffee and initiating a social interaction with a peer; and (ii) receiving verbal praise for each step of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
44
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 10 publications
2
44
1
1
Order By: Relevance
“…Empirical research supports video modeling as an effective pedagogical procedure that may produce quick skill acquisition (Allen, Wallace, Renes, Bowen, & Burke, 2010;Bidwell & Rehfeldt, 2004). Further, video modeling has been used to teach a variety of different skills including daily living skills (Shipley-Benamou, Lutzker, & Taubman, 2002), task analyses (Bellini & Akullian, 2007), social skills (Apple, Billingsley, & Schwartz, 2005;Maione & Mirenda, 2006), and vocational skills in young adults with ASD (Kellems & Morningstar, 2012).…”
Section: Abstract Video Modeling Adls Autism Spectrum Disordermentioning
confidence: 99%
“…Empirical research supports video modeling as an effective pedagogical procedure that may produce quick skill acquisition (Allen, Wallace, Renes, Bowen, & Burke, 2010;Bidwell & Rehfeldt, 2004). Further, video modeling has been used to teach a variety of different skills including daily living skills (Shipley-Benamou, Lutzker, & Taubman, 2002), task analyses (Bellini & Akullian, 2007), social skills (Apple, Billingsley, & Schwartz, 2005;Maione & Mirenda, 2006), and vocational skills in young adults with ASD (Kellems & Morningstar, 2012).…”
Section: Abstract Video Modeling Adls Autism Spectrum Disordermentioning
confidence: 99%
“…Video modeling has been shown to increase a variety of skills such as social skills (MacDonald, Clark, Garrigan, & Vangala, 2005), vocational skills (Kellems & Morningstar, 2012), play skills (Shipley-Benamou, Lutzker, & Taubman, 2002) and participation in the academic curriculum (Hart & Whalon, 2012). Video modeling has also been demonstrated to teach domestic skills such as coffee preparation (Bidwell & Rehfeldt, 2004), a major component of the restaurant. Video was taken using an iPad from the preparers' point of view for each step in the preparation of the menu items.…”
Section: Step 6: Use Research-based Training Methodsmentioning
confidence: 99%
“…It is an intervention which uses video modeling instead of live modeling for teaching a new behavior or changing an existing one; it is implemented by getting learners to watch all the steps of a target behavior from a video before being taught (Bellini, Akullian, & Hopf, 2007;Charlop-Christy, Le, & Freeman, 2000;Nikopoulos & Keenan, 2006;Sansosti & Powell-Smith, 2008). Coupled with technological advancements, much research has shown the widespread use of video modeling for teaching social skills (Akmanoğlu & Tekin-İftar 2011;Avcıoğlu, 2013;Bellini et al, 2007;Bidwell & Rehfeldt, 2004;Buggey, 2005;Charlop-Christy & Daneshvar, 2003;Charlop-Christy et al, 2000;D'Ateno, Mangiapanell, & Taylor, 2003;Emecen, 2008;Graetz, Mastropieri, & Scruggs, 2006;Kroeger, Schultz, & Newsom, 2007;Nikopoulos & Keenan, 2003;Olçay-Gül & Vuran, 2010). Examining the research in terms of participant characteristics, with the exception of three that had been conducted with individuals with intellectual disabilities (Avcıoğlu, 2013;Bidwell & Rehfeldt, 2004;Emecen, 2008), all were seen to be conducted with individuals with autism spectrum disorder (ASD) or Asperger's Syndrome.…”
mentioning
confidence: 99%
“…Coupled with technological advancements, much research has shown the widespread use of video modeling for teaching social skills (Akmanoğlu & Tekin-İftar 2011;Avcıoğlu, 2013;Bellini et al, 2007;Bidwell & Rehfeldt, 2004;Buggey, 2005;Charlop-Christy & Daneshvar, 2003;Charlop-Christy et al, 2000;D'Ateno, Mangiapanell, & Taylor, 2003;Emecen, 2008;Graetz, Mastropieri, & Scruggs, 2006;Kroeger, Schultz, & Newsom, 2007;Nikopoulos & Keenan, 2003;Olçay-Gül & Vuran, 2010). Examining the research in terms of participant characteristics, with the exception of three that had been conducted with individuals with intellectual disabilities (Avcıoğlu, 2013;Bidwell & Rehfeldt, 2004;Emecen, 2008), all were seen to be conducted with individuals with autism spectrum disorder (ASD) or Asperger's Syndrome. Research studies have additionally been seen carried out with individuals between the ages of 3 and 15; only one research has been conducted with adults (Bidwell & Rehfeldt, 2004) and none have been conducted with individuals between the ages of 18 and 25, the age of emerging adulthood.…”
mentioning
confidence: 99%
See 1 more Smart Citation